PENGARUH PEMUPUKAN FOSFOR DAN KALIUM TERHADAP PERTUMBUHAN TANAMAN KELAPA SAWIT (Elaeis Guineensis Jacq.) DI PEMBIBITAN UTAMA - Sudradjat -; Nindyta Agustina Siagian (Universitas Trunojoyo Madura, 2014)
Oil palm (Elaeis guineensis Jacq.) is one of plantation commodities that contribute to foreign exchange. Palm oil production is influenced by the expansion of the area and intensification using the fertilization at main nursery and plantation. Macro elements such as N, P, and K required by the oil palm are in large quantities. The study was conducted from November, 2011 to May, 2012 at Cikabayan Experimental Station, IPB Darmaga Campus, Bogor. The treatment was laid-out in a factorial randomized block design with three replications. The first factor was P: 0, 3.00, 6.00, and 12.00 g P plant-1 ; and the second was K: 0, 9.00, 18.00 and 36.00 g K plant-1. The results of the study showed that phosphor did not influence the plant height, number of frond, number of chlorophyll, and stem diameter. Potassium fertilizer influenced the stem diameter at 24 weeks after planting (WAP). There were the interaction between P and K on stem diameter variable at 16 and 20 WAP.Keywords : Fertilizer, phosphor, potassium, Elaeis Guineensis Jacq.